PEMANFAATAN DATA PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK KAJIAN PELAYANAN HALTE BIS TRANS JOGJA DI WILAYAH PERKOTAAN YOGYAKARTA - , HAYUWINDAR PAKSI WIRAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Trans Jogja is the Yogyakartaâ¢s main public transport which uses the âBus Rapid Transit\" system. The site an d location of shelters place an important role in the services level toward Trans Jogjaâ¢s users. The purposes of this study were (1) to determininate the potential level of inhabitant trip production in Yogyakarta, (2) to determininate the potential distribution of trip attraction in Yogyakarta, (3) to determininate the range of âTrans Jogjaâ¬ shelter coverage areas on existing locations, and (4) to determininate the ability of service level each shelter in terms of the location, the distribution of trip production and trip attraction. Urban areas in question is urban morphology with physical limitations Definition of the service level for a shelter considering the variable of inhabitant trip generation and attraction, and coverage area of shelter. Trip generation and attraction were identified from the data combination of the visual interpretation of remote sensing imagery and secondary data. Visual interpretation was carried out to identify land use consist of residental areas, educational areas, office areas, trade areas, service areas, and industrial areas. Settlement areas were assumed as the origin of trip generation and the rests were the destination. Coverage area was analyzed by using the network analyst. The service level of the shelter was analyzed on the basis of the ratio of trip production and trip attraction areas that was in coverage area. In urban areas, level of the trip production was higher when it was closer to the downtown. The highest level of inhabitant trip attraction referred to the educational areas while the lowest level referred to the industrial areas. The coverage area of shelter was 2964.51 hectares or 17.85 % of all urban areas of Yogyakarta. The highest service level of the shelter was on FK UGM shelter while the lowest one on Instiper 1 shelter. Keywords: remote sensing, geographic information systems, trip production, trip attraction, coverage area, bus stop, trans jogja